Growth, flowering and fruiting behaviour of different blueberry (Vaccinium spp) genotypes under mid hill conditions of Himachal Pradesh, India - NEGI, N D; UPADHYAY, S K (The Indian Journal of Agricultural Sciences, 2018)
Four southern highbush blueberry (Vaccinium spp. ) cultivars, viz. Jewel, Misty, Gulf Coast and Sharpblue along with Austin, and Alapaha (Rabbiteye) were studied for their vegetative growth, flowering and fruiting behaviour at CSKHPKV, Palampur, Himachal Pradesh during the year 2015-16. A significant variation was observed for annual shoots/cane growth and growth pattern among these genotypes. Southern highbush cultivar Jewel produced maximum (49.05 cm) shoots/cane length with vigorous growth, closely followed by a rabbiteye cultivar cv. Austin (48.36 cm) and minimum shoot growth (39.02 cm) was observed in Alapaha. The growth rate at different interval was also recorded and it was observed maximum at D2-3 intervals in all genotypes.The results also showed significant variation with respect to various foliar characters, viz. leaf size, specific leaf area, number of flowers/cluster, corolla size (length and breadth), number of stamens/flower and color of corolla. All southern highbush blueberry cultivars were earliest to flower as compared to rabbiteye. Similarly, a significant variation was observed for number of flowers and fruits/cluster among genotypes. Gulf Coast had maximum (8.78 flowers/cluster) number of flowers/cluster followed by Jewel (7.67 flowers/cluster) another southern highbush blueberry cultivar. The harvesting of southern highbush cultivars, viz. Misty and Gulf Coast was earliest among other genotypes and both rabbiteye blueberries the harvesting was late starting from 21 May in Alapaha and 27 May in Austin. However, the yield of individual cultivars was not recorded but cumulative yield at the end of harvesting it was observed to be 200-250 g/bush (data not presented). The southern highbush blueberries such as Jewel, Misty, Gulf Coast and Sharpblue have shown encouraging results with satisfactory growth, flowering and fruiting thus they can be grown in Himachal Pradesh and areas prevailing similar agroclimatic conditions in India.